Hospital Efficiency In Turkey: Metafrontier Analysis - Tunca, Halil; Yesilyurt, Filiz (European Scientific Journal, ESJ, 2016)
Turkey has the highest health spending on hospitals within OECD. Therefore measuring efficiency of hospitals is crucial to improve the health care. In line with this purpose Turkey experienced major reforms in healthcare since 1980s’. This paper focuses on the healthcare system for the Aegean Region of Turkey. The data obtained from Health Statistics Yearbook 2007 and our data covers 135 hospitals. Because of the heterogeneity across hospitals we used DEA Meta frontier analysis. The results show that the technical efficiencies with respect to group frontier and meta-frontier training-research hospitals and the medical faculty hospitals are higher than state and private hospitals. The results also indicate that the variation of technology gap ratio (TGR) is high for training-research hospitals and the medical faculty hospitals. Furthermore TGR for private and state hospitals are high and close to each other.